Chapter 4. Work Through the Valley: Plan - Jones, Loretta (Ethn Dis, 2009)
This first of three chapters on the Valley stage, or main work of a Community-Partnered Participatory Research (CPPR) initiative, concerns the planning phase of the work cycle. The main goal of this phase is to develop an action plan, which clarifies the goals, methods, responsible individuals, and timeline for doing the work. Further, this chapter reviews approaches, such as creativity and use of humor, that help level the playing field and assure community co-leadership with academic partners in developing effective action plans.